PREDICTION OF LONG-TERM NEUROLOGICAL CONSEQUENCES OF CORONAVIRAL INFECTION USING NEUROTROPIC AUTOANTIBODIES - Firuza Kh. Inoyatova; Gulnora K. Rakhmatullaeva; Nigina A. Vakhobova; Umida S. Salikhodjaeva (Central Asian Journal of Medicine, 2022)
Today, amid the ongoing COVID-19 pandemic, it has become clear that SARS-CoV-2 infection can have long-term consequences, even after asymptomatic or mild acute cases, raising concerns about the consequences of COVID-19. The terms “long-COVID-19”, “chronic COVID-19”, “post-COVID-19 syndrome” have appeared. Patients who have had COVID-19 often have fatigue, cognitive and psycho-emotional disorders, which are often referred to as "brain fog", and the possibility of developing neurodegenerative diseases is also discussed. The exact pathophysiological mechanisms of the development of the neurological long-term consequences of COVID-19 have not been established, but at the same time, numerous links are emerging between the post-COVID-19 syndrome, immunological changes, and neurotransmission dysfunction in the brain. Using method of immunochemical analysis ELI-Neuro-Test, developed by Professor A.B. Poletaev, we analyzed an individual profile of serum immunoreactivity, depending on changes in the relative content of IgG autoantibodies directed to 12 autogens of the nervous system. We identified in patients who underwent COVID-19 immunochemical signs of damage to the GABAergic (58.6%), opioid (37.9%), serotonergic (20.7%), cholinergic (13.8%) neurotransmitter systems, and also markers of axonal damage (20.7%), demyelination (10.3%) and reactive astrogliosis (24.1%). However, given the small sample size, further research is required.